Relatório Final do Estágio Curricular Obrigatório do Curso de Medicina Veterinária realizado no Hospital Veterinário Ufape, no Serviço de Nutrologia Veterinária do Hospital Veterinário da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo FMVZ/USP e no Serviço de Nutrição Clínica de Cães e Gatos do Hospital Veterinário Governador Laudo Natel da FCAV/UNESP - Caso de interesse: Síndrome de Realimentação a esclarecer em cão sob cuidados de terapia intensiva - Silva, Letícia Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
O presente relatório descreve as atividades desenvolvidas durante o estágio curricular obrigatório do curso de Medicina Veterinária, realizado no Hospital Veterinário Ufape, no Serviço de Nutrologia Veterinária do Hospital Veterinário da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo (FMVZ/USP) e no Serviço de Nutrição Clínica de Cães e Gatos do Hospital Veterinário Governador Laudo Natel da FCAV/UNESP. As atividades envolveram o acompanhamento nutricional de cães e gatos em internação, unidade de terapia intensiva e atendimento ambulatorial, incluindo avaliação do estado nutricional, cálculo de necessidades energéticas, prescrição de dietas, manejo de sondas enterais e monitoramento clínico-laboratorial. Como estudo de caso, foi apresentada a suspeita de Síndrome de Realimentação em um cão sob cuidados intensivos, com enfoque nos distúrbios metabólicos associados e na importância da introdução gradual da nutrição e do monitoramento eletrolítico.

This report describes the activities carried out during the mandatory curricular internship of the Veterinary Medicine program, conducted at the UFAPE Veterinary Hospital, at the Veterinary Nutrology Service of the Veterinary Hospital of the School of Veterinary Medicine and Animal Science, University of São Paulo (FMVZ/USP), and at the Clinical Nutrition of Dogs and Cats Service of the Governor Laudo Natel Veterinary Hospital, FCAV/UNESP. The activities included nutritional follow-up of dogs and cats in hospitalization, intensive care units, and outpatient settings, encompassing nutritional status assessment, calculation of energy requirements, diet prescription, management of enteral feeding tubes, and clinical and laboratory monitoring. As a case study, a suspected case of Refeeding Syndrome in a dog under intensive care was presented, focusing on the associated metabolic disturbances and the importance of gradual nutritional reintroduction and electrolyte monitoring.
Final Report of the Mandatory Curricular Internship of the Veterinary Medicine Program, carried out at the UFAPE Veterinary Hospital, at the Veterinary Nutrology Service of the Veterinary Hospital of the School of Veterinary Medicine and Animal Science, University of São Paulo (FMVZ/USP), and at the Clinical Nutrition of Dogs and Cats Service of the Governador Laudo Natel Veterinary Hospital, FCAV/UNESP: Case of interest: Refeeding Syndrome to be clarified in a dog under intensive care.
Keywords: Tratamento intensivo; Cães; Alimentação parenteral